(untitled) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2026)
This study aimed to evaluate the effect of fermented Sorghum bicolor-Indigofera zollingeriana (Sorinfer) silage at distinct levels on the performance of local rams. Studies were conducted over 7 weeks using 20 rams, with an initial body weight of 20,90±3,72 kg. Rams were divided into 5 treatments with 4 replicates, consisting of 100% field grass (P0), 75% P0 + 25% Sorinfer (P1), 50% P0 + 50% Sorinfer (P2), 25% P0 + 75% Sorinfer (P3), 100% Sorinfer (P4). Parameters measured were dry matter (DM), ash, crude protein (CP), crude fat (CF), crude fiber (CFi), total digestible nutrient (TDN), and daily weight gain. Data were analyzed using Analysis of Variance (ANOVA), and if a difference was detected, the Duncan Multiple Range Test was used. Feed treatment had a significant effect (p<0,05) on DM, ash, CP, CF, CFi, TDN, and daily weight gain. The finding is that using Sorinfer results in up to a 75% increase in intake of DM, ash, CP, CF, CFi, TDN, and daily weight gain.